Consultant paediatricians and child safeguarding: confidence in competences. (4th April 2011) - Hacking, K A; Green, P; Payne-James, J J; Thurlbeck, S
Abstract : Introduction: Safeguarding children is a fundamental responsibility of paediatricians but perceived as an increasingly unattractive task against a backdrop of adverse publicity from serious complaints. All paediatric consultants should be competent to undertake child safeguarding work relevant to their professional role. Aims: To determine (a) whether consultant paediatricians are appropriately trained to have confidence in safeguarding competencies, and (b) consultants' self-rated competencies, knowledge and attitudes at child safeguarding level 3. Methods: A questionnaire was sent to all substantive consultant paediatricians in a teaching hospital. Respondents rated themselves against Level 3 generic competencies outlined in the 2006 intercollegiate document 'Safeguarding Children and Young People: Roles and Competencies'. Results: 27/28 questionnaires were completed. Only one respondent had undertaken annual safeguarding training. Self-rating of competence on 13 aspects of child safeguarding ranged from 11% to 81%. Particular areas of self-rated low competence were (a) interpretation of possible sexual abuse and (b) undertaking forensic procedures. Most respondents rated themselves as competent in (a) assessing risk and harm, (b) multiagency working and (c) child protection conferences. 52% of respondents reported low levels of knowledge about local safeguarding boards; 81% felt they had adequate knowledge of multiagency frameworks. More than half of respondents expressed a feeling of dislike of safeguarding work. None wished to increase workload in this area. 37% did not feel confident in child safeguarding, however 81% were in agreement that involvement in child protection is their duty. Conclusions: Paediatricians appear to lack elements of training to give them confidence in all safeguarding competencies and more than half had reservations about working in this area. The national recommendations for safeguarding are not being optimally achieved by all consultant paediatricians. Efforts need to be made to improve access to and availability of continued training and professional support. Such intervention should increase paediatricians' confidence and thus willingness to undertake safeguarding work, benefiting all stakeholders. The recent work by the RCPCH advisory group on Child Protection Clinical Networks may provide a framework to address the current shortcomings.